AUSTRALIAN HEALTH POLICY REVIEW: SOUTH AUSTRALIA’S ORAL HEALTH PLAN - Rommel Maglaya (Scholar Express Journals, 2021)
Oral health issues could have a detrimental effect on a person's quality of life and are more common in older people. People who maintain good dental hygiene demand reduced health expenses. This trend is anticipated to continue, with over 75% of baby boomers entering long-term care facilities with the majority of their natural teeth in place (Haumschild & Haumschild, 2009). Irrespective of age, a healthy mouth has a tremendous influence on overall health. It might be the difference between children attending school consistently or not. Not only may poor dental health raise the risk of oral cancer, but it can also impair older adults' ability to eat, speak, and socialise (The Scottish Health Council, 2017).
Keywords: Oral health; hygiene; healthy mouth